1978
DOI: 10.1111/j.1399-6576.1978.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Apnoea after Suxamethonium: An Analysis of the First 225 Cases Reported to the Danish Cholinesterase Research Unit

Abstract: During the last 4 years, 225 patients have been referred to the Danish Cholinesterase Research Unit following an episode of prolonged apnoea after suxamethonium. Fourteen patients (6.2%) were found to have a low serum cholinesterase activity due to an acquired deficiency (for instance, liver disease, chronic debilitating disease or carcinoma). One hundred and forty-eight patients (65.8%) had an inherited abnormal serum cholinesterase, and 105 of these patients (46.7%) were homozygous for the atypical enzyme (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…As early as 1978, the Danish Cholinesterase Research Unit reported that 13% of individuals with abnormal SC responses were unable to be typed by inhibitor-identified alleles (2 ), an observation reinforced 4 years later by Morgan (4 ), who suggested that up to 8 -10% of patients were potentially misdiagnosed because of difficulties with phenotyping. Phenotype studies are prone to inaccuracy when enzyme amounts are low, but additional problems of variable enzyme response in different substrates and a diagnostic range of 10 phenotypes contribute to difficulties with identification.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…As early as 1978, the Danish Cholinesterase Research Unit reported that 13% of individuals with abnormal SC responses were unable to be typed by inhibitor-identified alleles (2 ), an observation reinforced 4 years later by Morgan (4 ), who suggested that up to 8 -10% of patients were potentially misdiagnosed because of difficulties with phenotyping. Phenotype studies are prone to inaccuracy when enzyme amounts are low, but additional problems of variable enzyme response in different substrates and a diagnostic range of 10 phenotypes contribute to difficulties with identification.…”
mentioning
confidence: 97%
“…cases) (2 ). Hence, the identification of individuals with inherited BChE variants remains within the province of the laboratory because the demonstration of low plasma cholinesterase activity (BChE) and abnormal enzyme phenotype (defined by responses to dibucaine and fluoride inhibitors) quantify the degree of impairment and confirm its hereditary basis.…”
mentioning
confidence: 99%
“…8 However, respiratory depression due to PSC deficiency rarely exceeds 240 min. 2,4 Al-Jafari et al 9 suggested that the CY effect on PSC is reversible, after demonstrating inhibition did not vary according to the length of preincubation in vitro. Walker et al 8 showed that CY inhibits PSC in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Other coexisting factors such as abnormal enzyme genotype might account for the prolonged neuromuscular blockade in some of the cases reported previously. 2,4 Prolonged apnea after anesthesia is extremely rare in patients receiving CY despite its extensive use. In the case described, the complication developed 9 h after the completion of high-dose CY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation